Preparation method of silicon dioxide nanobelt based on bubble rupture and application of silicon dioxide nanobelt to adsorption of heavy metal lead
The bubble bursting method for preparing amino-functionalized silica nanobelts addresses the challenges of adsorbent preparation and sedimentation, enhancing lead ion removal efficiency in aqueous solutions.
Patent Information
- Application Number
- CN202411286072.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2024-12-13
AI Technical Summary
Existing adsorbents for lead ions in aqueous solutions face challenges in preparation methods, adsorption performance, and sedimentation during the adsorption process, leading to inefficient lead removal and increased costs.
A bubble bursting method is used to prepare amino-functionalized silica nanobelts through an oil-in-water nanoemulsion with silane coupling agents, inducing droplet deformation for controlled morphology and size, followed by surface modification to enhance adsorption performance.
The method achieves continuous, low-energy preparation of silica nanobelts with excellent adsorption performance, avoiding sedimentation and improving lead ion removal efficiency.
Smart Images

Figure CN119114015A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of preparation of environmentally friendly functional materials, and relates to a method for preparing an adsorbent suitable for effectively adsorbing lead ions in an aqueous solution, and in particular to a method for preparing a silica nanobelt adsorbent by a bubble bursting method and its application in heavy metal pollution treatment. Technical Background
[0002] Lead (Pb) is an important industrial metal with a density greater than 4.5g / cm 3 , with a relative atomic mass of 207.2, has good ductility and plasticity, and is widely used in military industry, metallurgy, shipbuilding and marine engineering and other industries. In recent years, due to the increase in demand for lead, lead emissions caused by industrial processes such as lead mining, production and use, and manufacturing and processing have exceeded 150% of natural emissions, causing serious lead pollution. In addition, the use of lead in industries such as battery manufacturing, oil refining, coatings, pigments, metal plating and finishing, glass and ceramics, steel, and power plants is the main source of lead waste. In particular, the incomplete recycling of lead-acid batteries has led to lead pollution. A survey found that some cosmetics and water supply pipes can also increase the risk of lead exposure.
[0003] Lead pollution caused by human activities is mainly distributed in water bodies, soil, atmosphere and organisms, causing varying degrees of environmental pollution and food chain pollution. Air pollution is mainly caused by lead-containing smoke and exhaust gas produced by industrial processes such as volcanic eruptions and metal smelting. Foreign scholars have found that lead pollution to the atmosphere is closely related to PM10 particles. Lead-containing smoke or particles in the air are one of the sources of soil lead pollution through sedimentation. Studies have shown that in developing countries such as India, lead pollution in the soil seriously threatens arable land resources, resulting in a significant decrease in soil bacterial diversity, weakened soil fertility and soil self-purification ability, which in turn seriously affects the yield and quality of crops, and also pollutes surface water and groundwater through rainwater, endangering human life and safety. Lead pollution in water bodies is mainly caused directly or indirectly by industrial wastewater. Due to the ionic Pb 2+ Good water solubility leads to fast migration rate, making Pb 2+ Pollution is more persistent and more difficult to control. In addition, Pb 2+ Pollution is highly concealed, making it easy to be transmitted and accumulated along the food chain, eventually causing food chain pollution. Even if the lead concentration in the environment is relatively low, after accumulation and amplification through the food chain, the toxicity increases, which will seriously threaten human life and health. Therefore, the effective removal of heavy metal lead in water bodies is of great significance to the ecological environment and human health.
[0004] At present, the research on Pb in surgical water 2+The main removal methods include chemical precipitation, ion exchange, membrane separation, solution extraction and adsorption. The adsorption method has the advantages of simple operation and low cost, and has been widely used to remove or recover Pb in aqueous solution. 2+ . The design of the adsorbent morphology and surface function has a positive promoting effect on enhancing the lead removal effect. Commonly used lead ion adsorbents include low-priced adsorbents such as agricultural waste, but the subsequent surface modification process is complicated and also increases the cost. Other common high specific surface area nanoadsorbents include nano metal oxides, covalent organic frameworks (COFs), graphene nanosheets and nano silica materials, but these adsorbents still face defects in preparation methods and adsorption performance. In addition, during the adsorption process, the adsorbent is prone to sedimentation, resulting in insufficient utilization of the adsorbent or a long adsorption time. Therefore, by designing the nanobelt structure morphology of the adsorbent to avoid sedimentation or prolong the sedimentation time, the lead removal performance can be effectively enhanced. Summary of the invention
[0005] In view of the problems in the existing lead ion adsorbent synthesis technology, the present invention first uses the bubble bursting method to prepare an oil-in-water (O / W) nanoemulsion, and uses a silane coupling agent with strong hydrophobicity after hydrolysis to induce the deformation of nanodroplets to prepare amino-functionalized silica nanobelts. This method can achieve continuous and low-energy preparation of silica nanobelt adsorbents, and can achieve one-step preparation of functionalized silica nanotubes, nanobowls and nano hollow spheres. Subsequently, it is applied to the treatment of heavy metal lead in aqueous solution through surface post-modification, showing excellent adsorption performance.
[0006] The invention solves the problems of difficult preparation of silicon dioxide nanobelts, difficult thickness control and easy sedimentation of adsorbents. It uses O / W nanoemulsion as a droplet reactor, uses the hydrolysis and condensation of silane coupling agents to regulate the hydrophilicity and hydrophobicity of the droplet interface, induces droplet deformation, and achieves morphology and size regulation by regulating the amount of silane coupling agents. It is then applied to the treatment of lead-containing wastewater and exhibits excellent adsorption performance.
[0007] The technical solution adopted by the present invention is:
[0008] A method for preparing silicon dioxide nanoribbons based on bubble collapse comprises the following steps:
[0009] (1) Using a CTAB aqueous solution as the water phase and a mixture of n-dodecane and a silane coupling agent as the oil phase, the oil phase is slowly added to the surface of the water phase with a certain thickness, air is passed into the water phase, the flow rate of bubbles generated and the outlet diameter of the air pipe are controlled to ensure that the bubbles are orderly broken at the water / oil / air three-phase interface, and react at room temperature to prepare a silica nanomaterial;
[0010] (2) Weigh 1-ethyl-(3-dimethylaminopropyl)carbodiimide (EDC), N-hydroxysuccinimide (NHS) and L-cysteine and disperse them in deionized water, add a small amount of sodium hydroxide to completely dissolve the three reagents, and then add the silica nanomaterial obtained in step (1) to the mixed solution. After the reaction is completed, collect the product by centrifugation to obtain a functionalized nanobelt adsorbent.
[0011] In step (1), the concentration of the CTAB aqueous solution is 8×10 -3 -10 -2 mM;
[0012] In step (1), when the silane coupling agent in the oil phase is 1,2-bis(triethoxysilyl)ethane TBES and 3-aminopropyltriethoxysilane APTS, the usage ratio of n-dodecane, TBES and APTS is (3-9 mL): (0.1-1.2 mL): (0.02-0.3 mL);
[0013] Alternatively, when the silane coupling agent in the oil phase is 1,2-bis(triethoxysilyl)ethane TBES, 3-aminopropyltriethoxysilane APTS and 3-chloropropyltrimethylsilane CPTMS, the dosage ratio of n-dodecane, TBES, APTS and CPTMS is (3-9 mL): (0.1-1.2 mL): (0.02-0.3 mL): (0.01-0.2 mL);
[0014] Alternatively, when the silane coupling agent in the oil phase is 1,2-bis(triethoxysilyl)ethane TBES and N-aminoethyl-γ-aminopropyltrimethoxysilane AAPTS, the usage ratio of n-dodecane, TBES and AAPTS is (3-9 mL): (0.1-1.2 mL): (0.05-0.2 mL).
[0015] In step (1), the thickness of the oil layer on the surface of the water phase is 0.8-1.2 mm;
[0016] In step (1), the gas flow rate is 0.05-0.15 L / min; the outlet diameter of the ventilation tube is 1.5-2.5 mm;
[0017] The reaction time at room temperature is 36-60h.
[0018] In step (2), the usage ratio of EDC, NHS, L-cysteine and silica nanomaterial is (1.2-3.6 g): (0.5-1.5 g): (0.3-0.9 g): (1-4 g), and the reaction time is 9-15 h.
[0019] The silicon dioxide nanobelt prepared by the present invention is used for adsorbing heavy metal lead.
[0020] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0021] The present invention prepares nanoemulsion by low-energy emulsification bubble bursting method, and uses it as a template, utilizes silane coupling agent pairs, and the interface regulation performance of template droplets to induce droplet deformation, thereby realizing the preparation of silica nanoribbons, which shows obvious structural advantages in the treatment of lead-containing wastewater.
[0022] The present invention uses the hydrolysis condensation of the silane coupling agent to induce droplet deformation to achieve regulation of the adsorbent morphology structure, avoiding the need for multiple templates in preparing multiple morphology materials by the traditional template method. In addition, the method is simple to operate, can be prepared continuously and has low reaction requirements.
[0023] The silicon dioxide nanobelt prepared by the present invention shows outstanding structural advantages in lead ion adsorption compared with other adsorbents of morphology prepared in the same period, and effectively avoids the problem of sedimentation of the adsorbent during the adsorption process. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 These are photos of the solution system before (a) and after (b) the formation of the nanoemulsion in Comparative Example 1 and a particle size distribution diagram of the nanoemulsion prepared in Example 1 (c).
[0025] Figure 2 These are the SEM images (a, c, d, e and f) of SR1-A, SR2-A, SR3-A, SR4-A and SR5-A prepared in Comparative Example 2, the SEM image (b) of SR2-a, and the SEM images (g, h and i) of SR3-B, SR4-B, SR5-B.
[0026] Figure 3 It is the SEM image of SR2-a2, SR3-a2, SR4-a2 and SR5-a2 prepared in Example 1.
[0027] Figure 4 are SEM images of SR2-A2, SR3-A2, SR5-A2 and SR3-A1 prepared in Example 1.
[0028] Figure 5 It is the SEM image of SR2-a3, SR3-a3, SR2-A3, SR3-A3, SR4-A3 and SR5-A3 prepared in Example 1.
[0029] Figure 6 TEM images of SR3-A, SR3-A3 and SR5-A3 prepared in Example 1.
[0030] Figure 7TEM mapping images (Si, O, C and N elements) of SR3-A, SR3-A3 and SR5-A3 prepared in Example 1.
[0031] Figure 8 It is the FT-IR spectra of SR3-A, SR3-A3 and SR5-A3 prepared in Example 1 (a) and SR3-D, SR3-3D and SR5-3D prepared in Example 2 (b).
[0032] Fig. 9 The effect of pH value on the adsorption of SR3-D, SR3-3D and SR5-3D prepared in Example 3 (a), the adsorption isotherms of SR3-D, SR3-3D and SR5-3D in Example 5 (b) and the distribution coefficient K in Example 5 d Curve (c).
[0033] Fig.10 The adsorption kinetics of SR3-D, SR3-3D and SR5-3D in Example 4 and their pseudo-first-order and pseudo-second-order kinetics (a), intraparticle diffusion (b) and Elovich model fitting (c).
[0034] Fig.11 The adsorption of Pb by SR3-3D in Example 5 2+ XPS full spectrum scan before and after (a), SR3-3D adsorbs Pb in Example 5 2+ High-resolution XPS spectrum of Pb4f (b), SR3-3D adsorbs Pb in Example 5 2+ Pre-N1s (c), O1s (d), S2p (e) and adsorbed Pb 2+ High-resolution XPS spectra of N1s (c1), O1s (d1), and S2p (e1). DETAILED DESCRIPTION
[0035] Comparative Example 1
[0036] Accurately weigh 0.0066g CTAB, dissolve it in 200mL deionized water, transfer it to a 250mL beaker and add n-dodecane to control the thickness of the oil phase to be about 1.0mm. Blow air through an oxygen pump, adjust the gas flow rate to 0.05-0.15L / min, and design the bubble outlet diameter to 2.0mm to ensure that the bubbles can pass through the oil-water interface one by one in order. Continue to introduce bubbles at room temperature for 48h to obtain an oil-in-water (O / W) nanoemulsion.
[0037] like Figure 1 In the figure, there are photos of the solution system before (a) and after (b) the formation of the nanoemulsion and the particle size distribution diagram of the nanoemulsion (c), indicating that the nanoemulsion was successfully prepared by the bubble burst method.
[0038] Comparative Example 2
[0039] The bubble burst method was used to prepare a series of nano-silica materials. 200 mL of CTAB aqueous solution (9 × 10 -3 mM) as the water phase, 4.0mL of n-dodecane and a mixture of silane coupling agent TBES (0.1mL) and APTS (0.1mL) as the oil phase. During the experiment, the oil phase was slowly added to the surface of the water phase at a thickness of 1.0mm, the gas flow rate was controlled to 0.05-0.15L / min, and the outlet diameter of the vent pipe used was 2.0mm to ensure that the bubbles were orderly broken at the water / oil / air three-phase interface to form a nanoemulsion. The reaction was carried out at room temperature for 48h, and the product was obtained by centrifugation and named SR1-A.
[0040] Referring to the above method, when the silane coupling agent is 0.2 mL TBES and 0.05 mL APTS, the product is SR2-a.
[0041] When the silane coupling agent is 0.2 mL, 0.3 mL, 0.4 mL, 0.5 mL of TBES and 0.1 mL of APTS, products SR2-A, SR3-A, SR4-A and SR5-A are obtained respectively.
[0042] When the silane coupling agent is 0.3mL, 0.4mL, 0.5mL of TBES and 0.1mL of AAPTS, products SR3-B, SR4-B, and SR5-B are obtained, respectively.
[0043] SEM images of SR1-A, SR2-A, SR3-A, SR4-A, and SR5-A (a, c, d, e, and f), SEM image of SR2-a (b), and SEM images of SR3-B, SR4-B, and SR5-B (g, h, and i)
[0044] like Figure 2 In the figure, there are SEM images (a, c, d, e and f) of SR1-A, SR2-A, SR3-A, SR4-A and SR5-A, SEM image (b) of SR2-a, and SEM images (g, h and i) of SR3-B, SR4-B and SR5-B, indicating that the increase of silane coupling agent TBES shortens the tubular structure.
[0045] Example 1
[0046] (1) The bubble bursting method was used to prepare a series of nano-silica materials. 200 mL of CTAB aqueous solution (9×10 -3mM) as the water phase, 4.0mL of n-dodecane and a mixture of silane coupling agents TBES (0.1mL) and APTS (0.1mL) as the oil phase. During the experiment, the oil phase was slowly added to the surface of the water phase at a thickness of 1.0mm, the gas flow rate was controlled to be 0.05-0.15L / min, and the outlet diameter of the vent pipe used was 2.0mm to ensure that the bubbles were orderly broken at the water / oil / air three-phase interface to form a nanoemulsion. The reaction was carried out at room temperature for 48h, and the product was obtained by centrifugation. When the silane coupling agents added to the oil phase were 0.2mL, 0.3mL, 0.4mL, 0.5mL of TBES, 0.05mL of APTS and 0.05mL of CPTMS, the products SR2-a2, SR3-a2, SR4-a2 and SR5-a2 were obtained respectively.
[0047] Referring to the above method, when the silane coupling agent added to the oil phase is 0.3 mL TBES, 0.1 mL APTS and 0.1 mL (or 0.05 mL) CPTMS, the product SR3-A1 (or SR3-A2) is obtained.
[0048] When the amount of silane coupling agent used is 0.2 mL (or 0.5 mL) TBES, 0.1 mL APTS and 0.05 mL CPTMS, the product SR2-A2 (or SR5-A2) is obtained.
[0049] When 0.2 mL (or 0.3 mL) TBES, 0.05 mL APTS and 0.03 mL CPTMS were added, the product SR2-a3 (or SR3-a3) was obtained.
[0050] When 0.2 mL, 0.3 mL, 0.4 mL, 0.5 mL of TBES, 0.1 mL of APTS and 0.03 mL of CPTMS were taken as silane coupling agents, products SR2-A3, SR3-A3, SR4-A3 and SR5-A3 were obtained, respectively.
[0051] like Figure 3 In the figure, the SEM images of SR2-a2, SR3-a2, SR4-a2 and SR5-a2 are shown, respectively, indicating that when the amount of silane coupling agent CPTMS is 0.05 mL, silica nanoribbons are formed, and with the increase of TBES, the ribbon structure is difficult to control.
[0052] like Figure 4 In the figure, the SEM images of SR2-A2, SR3-A2, SR5-A2 and SR3-A1 are shown, indicating that the amount of CPTMS greater than 0.05 mL and the excessive amount of silane coupling agent are not conducive to the formation of nanobelt structure.
[0053] like Figure 5In the figure, the SEM images of SR2-a3, SR3-a3, SR2-A3, SR3-A3, SR4-A3 and SR5-A3 are shown, indicating that reducing the amount of CPTMS to 0.03 mL is beneficial to the growth of ribbon structures, and the increase of TBES makes the silica nanoribbons longer.
[0054] like Figure 6 In the figure, the TEM images of SR3-A, SR3-A3 and SR5-A3 are shown, indicating that the silica nanoribbons have a large aspect ratio and an extremely thin thickness.
[0055] like Figure 7 In the figure, the TEM mapping images (Si, O, C and N) of SR3-A, SR3-A3 and SR5-A3 are shown, indicating their elemental compositions.
[0056] (2) Weigh 1.46 g EDC, 0.75 g NHS and 0.463 g L-cysteine and disperse them in 40 mL deionized water, add a small amount of sodium hydroxide to completely dissolve the three reagents. Then add silica nanobelts (SR3-A, SR3-A3 or SR5-A3 prepared in step (1)) to the mixture, react for 12 h, collect the product by centrifugation, and wash it three times with ethanol and three times with weak alkaline water (pH = 8). The functionalized nanobelt adsorbents obtained are SR3-D, SR3-3D and SR5-3D, respectively.
[0057] like Figure 8 In the figure, the FT-IR spectra of SR3-A, SR3-A3 and SR5-A3 (a) and SR3-D, SR3-3D and SR5-3D (b) are shown, indicating that the surface modification was successful.
[0058] Example 2
[0059] Accurately weigh 2.0 mg of adsorbent (SR3-D, SR3-3D or SR5-3D prepared in Example 1), add 4.0 mL of Pb 2+ The solution (100 mg / L) was placed in a constant temperature water bath oscillator. After 6.0 h, the supernatant was centrifuged and the remaining Pb was determined. 2+ The adsorption capacity of the adsorbent at different pH values (3.0-6.0) was calculated. All experiments were repeated three times.
[0060] like Fig. 9 In a, it is a curve diagram showing the effect of pH value on the adsorption of SR3-D, SR3-3D and SR5-3D, which shows that the adsorption performance of the three adsorbents is best when the pH is 6.
[0061] Example 3
[0062] Accurately weigh 2.0 mg of adsorbent (SR3-D, SR3-3D or SR5-3D prepared in Example 1), add 4.0 mL of Pb 2+ The solution was statically adsorbed for 1.0 min, 5.0 min, 10 min, 20 min, 40 min, 80 min and 160 min, and the supernatant was centrifuged and the residual Pb was detected by flame atomic absorption spectrometry. 2+ The adsorption capacity of each adsorbent was calculated, and all experiments were repeated three times.
[0063] like Fig.10 In the figure, the adsorption kinetics and pseudo-first-order and pseudo-second-order kinetics (a), intraparticle diffusion (b) and Elovich model fitting (c) of SR3-D, SR3-3D and SR5-3D are shown, indicating that the three adsorbents can reach adsorption equilibrium in 80 min.
[0064] Example 4
[0065] Prepare 4.0mL of Pb with different concentrations 2+ 2.0 mg of adsorbent (SR3-D, SR3-3D or SR5-3D) was added to each solution (50 mg / L, 100 mg / L, 150 mg / L, 200 mg / L and 250 mg / L) and placed in a 25°C water bath shaker. After 4.0 h, the supernatant was centrifuged and the remaining Pb in the supernatant was detected. 2+ The adsorption capacity of each adsorbent at different concentrations was calculated. All experiments were repeated three times.
[0066] like Fig. 9 b and Fig. 9 In c, the adsorption isotherms and distribution coefficients K of SR3-D, SR3-3D and SR5-3D are shown respectively. d The curve shows that SR5-3D has the largest adsorption capacity.
[0067] like Fig.11 In the figure, SR3-3D adsorbs Pb 2+ The XPS full spectrum scan before and after, the high-resolution XPS spectrum of Pb4f (b), the high-resolution XPS spectrum of N1s (c), O1s (d), S2p (e) before adsorption and N1s (c1), O1s (d1), S2p (e1) after adsorption, indicate that SR3-3D utilizes the amino, carboxyl and disulfide bonds on its surface to achieve effective adsorption of lead ions.
Claims
1. A method for preparing silicon dioxide nanoribbons based on bubble collapse, characterized in that: The steps include: (1) Using a CTAB aqueous solution as the water phase and a mixture of n-dodecane and a silane coupling agent as the oil phase, the oil phase is slowly added to the surface of the water phase with a certain thickness, air is passed into the water phase, the flow rate of bubbles generated and the outlet diameter of the air pipe are controlled to ensure that the bubbles are orderly broken at the water / oil / air three-phase interface, and react at room temperature to prepare a silica nanomaterial; (2) Weigh 1-ethyl-(3-dimethylaminopropyl)carbodiimide (EDC), N-hydroxysuccinimide (NHS) and L-cysteine and disperse them in deionized water, add a small amount of sodium hydroxide to completely dissolve the three reagents, and then add the silica nanomaterial obtained in step (1) to the mixed solution. After the reaction is completed, collect the product by centrifugation to obtain a functionalized nanobelt adsorbent.
2. The preparation method according to claim 1, characterized in that In step (1), the concentration of the CTAB aqueous solution is 8×10 -3 -10 -2 mM.
3. The preparation method according to claim 1, characterized in that: In step (1), when the silane coupling agent in the oil phase is 1,2-bis(triethoxysilyl)ethane TBES and 3-aminopropyltriethoxysilane APTS, the usage ratio of n-dodecane, TBES and APTS is (3-9 mL): (0.1-1.2 mL): (0.02-0.3 mL).
4. The preparation method according to claim 1, characterized in that: In step (1), when the silane coupling agent in the oil phase is 1,2-bis(triethoxysilyl)ethane TBES, 3-aminopropyltriethoxysilane APTS and 3-chloropropyltrimethylsilane CPTMS, the usage ratio of n-dodecane, TBES, APTS and CPTMS is (3-9 mL): (0.1-1.2 mL): (0.02-0.3 mL): (0.01-0.2 mL).
5. The preparation method according to claim 1, characterized in that: In step (1), when the silane coupling agent in the oil phase is 1,2-bis(triethoxysilyl)ethane TBES and N-aminoethyl-γ-aminopropyltrimethoxysilane AAPTS, the dosage ratio of n-dodecane, TBES and AAPTS is (3-9 mL): (0.1-1.2 mL): (0.05-0.2 mL).
6. The preparation method according to claim 1, characterized in that: In step (1), the thickness of the oil layer on the surface of the water phase is 0.8-1.2 mm.
7. The preparation method according to claim 1, characterized in that: In step (1), the gas flow rate is 0.05-0.15 L / min; the outlet diameter of the ventilation tube is 1.5-2.5 mm; and the reaction time at room temperature is 36-60 h.
8. The preparation method according to claim 1, characterized in that: In step (2), the usage ratio of EDC, NHS, L-cysteine and silica nanomaterial is (1.2-3.6 g): (0.5-1.5 g): (0.3-0.9 g): (1-4 g), and the reaction time is 9-15 h.
9. Use of the silicon dioxide nanobelts prepared by the preparation method according to any one of claims 1 to 8 for adsorbing heavy metal lead.
